Digital optical measurement techniques and applications - Rastogi, Pramod K. 1951- (Artech House, 2015)
This new resource explains the principles and applications of today's digital optical measurement techniques. From start to finish, each chapter provides a concise introduction to the concepts and principles of digital optical metrology, followed by a detailed presentation of their applications